Profile of Age and Sex of Congenital Rubella Syndrome Patients with Congenital Heart Disease - Chaq El Chaq Zamzam Multazam; Mahrus A. Rahman; Wiwin Retnowati (Humanistic Network for Science and Technology (HNST), 2021)
Background: Rubella is an acute viral disease that often attacks vulnerable children and young adults throughout the world. Even though it only causes mild clinical illness, concern in the health world arises from its teratogenic potential resulting in congenital rubella syndrome (CRS). The most common abnormalities of CRS are hearing loss or deafness, eye defects and congenital heart defects. Purpose: To determine the profiles of age and sex in congenital rubella syndrome patients with congenital heart disease in Dr Soetomo Regional Public Hospital for the period of 2016-2018. Methods: This type of research was a descriptive study by collecting data on the age and sex in congenital rubella syndrome patients with congenital heart disease in Dr Soetomo Regional Public Hospital retrospectively through medical records of patients for the period of 2016-2018. Results: The most age group of congenital rubella syndrome patients with congenital heart disease in Dr Soetomo Regional Public Hospital for the period of 2016-2018 was the toddler (0-